Kukis feast : Cookies / Siti Nur Syaza Taheera Sheikh Abd Rahman ...[et al.] - Sheikh Abd Rahman, Siti Nur Syaza Taheera; Mohd Noor, Nurul Najwa; Mahmod, Khairuna Husna; Rosli, Nur Ain Amila; Rosli, Fatin Nur Ellyssa (2022)
A business plan is a vital document that each new company must have in place before one can begin operations. Because of the long-term operational business, it is critical to build up the business plan because a solid business plan should describe all of the estimated expenses and potential risks to each decision a firm takes. The goals of this business plan project are to develop an effective development strategy, determine future financial needs, and attract investors and lenders. Our company's name was Kukis Feast as the 'Kukis' is originated from English word, cookies. We were provided three sorts of cookies: Chocolate Chip cookies, Almond Red Velvet cookies, and SeaSalt Dark Chocolate cookies. We can classify our business mode as hybrid because customers can visit us in person or prefer to have our products delivered to them. We registered our company on 1 March 2022 and have started the operation on 13 June 2022 as our company date of commencement. The form of our company is Partnership. We have five members in total in our organization which the General Manager, the Administration Manager, the Marketing Manager, the Operation Manager and also Financial Manager. Kukis Feast mission statement is to produce high quality of product, provide excellent customer service, and provide job opportunities especially to a single mother and someone in need.